Approach-Method Interaction: The role of teaching method on the effect of context-based approach in physics instruction - Pesman, Haki; Ozdemir, Omer Faruk (Routledge Journals, Taylor & Francis Ltd, 2012)
The purpose of this study is to explore not only the effect of context-based physics instruction on students' achievement and motivation in physics, but also how the use of different teaching methods influences it (interaction effect). Therefore, two two-level-independent variables were defined, teaching approach (contextual and non-contextual approaches) and teaching method (traditional and learning cycle methods). Thus, a 2 x 2 factorial design was performed with four treatment groups, including 131 11th-grade students: (1) a traditional method with the non-contextual approach group, (2) a traditional method with the contextual approach group, (3) a learning cycle with the non-contextual approach group, and (4) a learning cycle with the contextual approach group. Prior to and just after the treatments, which took 5 weeks, pre-tests and post-tests on student achievement and motivation were administered. For the analysis of data, multivariate analysis of covariance, simple regressions and follow-up analysis of covariances were performed. Consequently, it was found that the effect of context-based approach on physics achievement is dependent upon the teaching method implemented. That is, the traditional method was observed to increase the effect of the contextual approach while the learning cycle decreased it. Related to the effects on motivation in physics, no evidence was found to claim a significant difference. Based on the findings of this study, further research is suggested for determining which teaching methods are more effective with the context-based approach on students' achievement and motivation in physics.
Keywords: Physics education; Context-based approach; Learning cycle; Motivation in physics; Physics achievement